Travel thru history. Discover Hoover Dam [videorecording (DVD)] (Travel thru history., 2019)
Marvel at the site of America's most famous water dam. Viewers learn about how the Hoover Dam was built, why it's necessary, and take a behind the scenes look at its inner workings